Improving swing performance and reducing discomfort with structured warm-ups in golf - Yusri, Hafizrie; Adnan, Aizzat; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Md Yusof, Yusandra; Abidin, Muhammad Amrun Haziq (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the impact of a four-week structured warm-up program on swing speed and injury risk among eighteen amateur male golfers. By comparing participants who performed dynamic stretches and golf-specific movements against a control group using the Trackman System and self-reported pain scales, the research investigates the biomechanical and preventive benefits of consistent pre-play routines. The findings aim to establish evidence-based guidelines to help amateur golfers optimize their performance and mitigate common issues such as lower back discomfort.